El cuidado, en el corazón de la ciencia (2021)
A pandemic world, crestfallen and full of fear, found an ally in science to help it get out of such a crisis. Focused on caring for and understanding this moment, scientists and thinkers have contributed their knowledge in the search for solutions. The challenge for humanity? Stop thinking in the short term.